Audyt kultury organizacyjnej - warunek konieczny implementacji zmian organizacyjnych - Tracz, Ewa (Diagnosing organizational culture – the precondition of organizational changes, 2006)
It is recognize that organizational culture has a powerful effect on the performance and long term effectiveness of organization. Organizational culture assessment is increasingly important because of the need to change and maintain stability in the face of increasingly turbulent external environments. Having a diagnostic instrument to identify organizational culture can be an especially useful tool in the effective management of organizational change. The article covers a description of the culture diagnosing steps and the two main strategies to assess culture: qualitative (holistic, metaphorical/language approach) and quantitative approach. It includes examples of this approaches.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 594-604